SOLUSI TRADE-OFF FUEL-FOOD DALAM PENGEMBANGAN BIODIESEL - Purba, Jan Horas V (LPPM Institut Bisnis dan Informatika Kesatuan, 2015)
This research is conducted as simulated analysis to respond an existing issue in Indonesia's palm oil industry. In the year 2015, world consumptions for CPO has reached 37.73%, and 31.96% for soybean oil (Oil World, 2015). Compared to the condition in 1960, this is a remarkable progress, where CPO only contributed 3.18%, and soybean oil on the other hand was in the highest rank with 12.29% of the world's total vegetable oil production. This also indicates that CPO has become one of the world's strategic commodities in the world's vegetable oils market. Ever since 2008, Indonesia has been successful in surpassing Malaysia 's domineering palm oil products, and leading the world's market of vegetable oils. Indonesia's export of CPO in 2015 was predicted to reach 21.8 tons and 14.78 tons for Malaysia. This shows Indonesia's tremendous role to feed the world. Due to biodiesel mandatory policy, the demands for CPO as biodiesel fuel will be increasing, and negatively affecting Indonesia 's export growths. Keyword : trade-off, biodiesel, CPO